Adelina Gurrea. Cuentos de Juana. Ed. Beatriz Álvarez Tardío. Manila: Instituto Cervantes de Manila, 2009. 292 pages. Jesús Balmori. Los pájaros de fuego. Ed. Isaac Donoso. Manila: Instituto Cervantes de Manila, 2010. 213 pages. Antonio M. Abad. El campeón. Ed. Salvador García. Quezon City: Ateneo de Manila University Press, 2013. 308 pages. - Park, Paula C. (Archīum Ateneo, 2014)
Excerpt: Instituto Cervantes plays a visible role in promoting events related to Hispanic culture and the study of the Spanish language in many countries. The Instituto Cervantes of Manila seems to have a more acute agenda since the Filipinos who decide to learn Spanish are, in a way, renewing the country’s historical ties to Spain. Put succinctly by Nick Joaquin in his essay “The Language of the Street” (1963) at a time when Spanish speakers had already diminished drastically: “Spanish is not dead in the Philippines; we unknowingly speak it every moment of our lives.” Hence, one of the objectives of the collection Clásicos hispano filipinos, launched in 2009 by Instituto Cervantes of Manila, is to recover the diverse voices within Philippine literature written in Spanish, and to present them in an accessible manner through annotated critical editions. The Instituto’s goal is to publish works by twentieth-century Filipino writers that have limited circulating copies or have never been published